PENGARUH PENGGUNAAN MEDIA INTERAKTIF BERBASIS H5P TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN SEJARAH KELAS X SMK ABDURRAB PEKANBARU - Mahdatul Hilda; Bunari, Bunari; Yuliantoro, Yuliantoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
History learning in school still faces problem such as low student and the limited use learning media, which affect student`s learning outcomes. This study aims to determine the effect of using interactive media based on HTML5 Package (H5P) on student learning outcomes in history learning for class X of SMK Abdurrab Pekanbaru. The study used a quasi-experimental method with a Pre-test–Post-test Non-Equivalent Control Group design. The instrument used was a learning outcome test in the experimental and control classes. The results showed that interactive media based on H5P can be applied well in history learning and has a significant influence on student learning outcomes. This was proven through a t-test with a Sig. (2-tailed) value of 0.026 < 0.05. In addition, the N-Gain value of the experimental class was in the medium–high category (64,26), higher than the control class (53.25). Thus, H5P media was proven to be more effective than conventional media in improving student learning outcomes.